Peran Komunikasi Antarpribadi Barista dalam Membangun Hubungan dengan Pelanggan Area 9 - Yulian Rizky Perdana; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
A barista has a new role now, not only cracking coffee, a barista must be able to communicate with customers for the progress of his coffee shop. Communicating in this study focuses on interpersonal communication of Barista coffee shop Area 9 to retain customers who come, all efforts in the context of communication from verbal and non-verbal, how to persuade and approach by seeing the same background from hobbies, musical tastes to exchange of insights. In addition, this can be used as a place to ask how customers think about the taste of coffee, the concept of the shop and the interior design of the coffee shop. Activeness in interacting will be of added value in consumer attractiveness because communicating with consumers not only adds a good impression but can also provide a sense of comfort and personal image to the barista and of course the image of the coffee shop Area 9. Interpersonal communication will play an effective role in developing the shop Coffee Area 9 if the barista at this coffee shop keeps things like this.